The effects of airmass history on new particle formation in the free troposphere: case studies - D. R. Benson; Li-Hao Young; Shan-Hu Lee; T. L. Campos; D. C. Rogers; J. Jensen (Atmospheric Chemistry and Physics, 2008)
Recent aircraft studies showed that new particle formation (NPF) is very active in the free troposphere. And, these observations lead to a new question: when does NPF not occur? Here, we provide case studies to show how different meteorological parameters affect NPF in the upper troposphere, using the aerosol size distributions measured at latitudes from 18° N–52° N and altitudes up to 14 km during the NSF/NCAR GV Progressive Science Missions. About 95% of the total samples showed the NPF feature with median number concentrations of particles with diameters from 4 to 9 nm (N4–9), 288±199 cm−3, and the total particle number concentrations with diameters from 4 to 2000 nm (N4–2000), 500±259 cm−3. Surface areas were in general very low in the free troposphere, 1.58±0.87 μm2 cm−3, which in part explains the high frequency of NPF measured in this region, but there was no distinctive difference in surface area for the NPF and non-NPF cases. Our case studies show that rather airmass history is more important for nucleation in this region. Weak- or non-events did not display uplifting of airmasses. On the other hand, strong NPF events were usually associated with uplifting of airmasses, although there were also NPF cases in which uplift did not occur, consistent with the previous observations (Young et al., 2007). NPF tends to easily occur in the free troposphere because of low surface areas and low temperatures (Carslaw and Kärcher, 2006), but because of the low aerosol precursors in this region, vertical motion (that can bring higher concentrations of aerosol precursors from low altitude source regions to higher altitudes) can play a critical role. Latitude dependence of new particles also shows higher particle concentrations in the midlatitude and subtropics tropopause region than in the tropics, consistent with Hermann et al. (2003).